Implementation of MVC in Food Ordering Application on Android Operating System Platform Case Study of RZ Rumah Barokah: - - Nistra, Nistrayani; Ariansyah; Suhartini (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
In the era of advancing technology, computer devices and their applications have become an integral part of daily life. Mobile computing, such as Tablet PCs and Smartphones, is increasingly dominant, with Android being one of the primary platforms chosen for application development due to its ease of use and flexibility. Android has penetrated various sectors, including the culinary industry, contributing significantly to business development and marketing. The food business in Indonesia continues to thrive with increasing consumer demand, yet faces challenges with intensifying competition. Amidst these challenges, business owners must actively seek strategies to expand market reach and consider external and internal factors affecting business development. RZ Rumah Barokah, as one of the home-based food businesses in Kota Prabumulih, is also confronted with these challenges. The business produces specialty foods as regional souvenirs but faces constraints in reaching a wider market. To address this issue, the development of an online sales system using information technology becomes a solution. By leveraging a website-based application, it is hoped that RZ Rumah Barokah can expand its marketing and promotional reach. The development method using Model View Controller (MVC) is expected to help separate logic, presentation, and processes efficiently in system development.